Catalytic oxidation of biomass to oxygenated chemicals with exceptionally high yields using H5PV2Mo10O40. (15th March 2018) - Lu, Ting; Hou, Yucui; Wu, Weize; Niu, Muge; Ren, Shuhang; Lin, Zengqi; Ramani, Vijay K.
Highlights: Biomass is effectively converted to oxygenated chemicals in H5 PV2 Mo10 O40  + methanol aq. solution. High carbon yields, 92.9% from glucose and 89.7% from cellulose, are obtained under 3 MPa O2. Acetalisation and etherification caused by methanol favor suppressing CO2 and enhancing the yields. The structural stability of catalyst H5 PV2 Mo10 O40 is increased by the addition of methanol. The catalyst H5 PV2 Mo10 O40 shows good reusability. Abstract: The transformation of biomass into platform chemicals is a key intermediate step to establish biomass-based sustainable chemical processes. The preparation of oxygenated chemicals by conversion of biomass is of significant conceptual and practical interest. In this work, an efficient catalytic system for carbohydrate-based biomass oxidation to oxygenated chemicals (including formic acid, dimethoxymethane and methyl formate) with O2 using H5 PV2 Mo10 O40 as catalyst is presented. Conversions of glucose and cellulose in a methanol/water medium achieved total product yields of oxygenated chemicals up to 92.9% and 89.7%, respectively (based on carbon). A conversion pathway to clarify the mechanism of product formation was proposed. Protecting reactive functional groups of sugars and reaction intermediates via acetalisation and etherification in methanol effectively suppressed CO2 formation and remarkably enhanced the production of oxygenated chemicals. The effect of solvent composition on catalyst H5 PV2 Mo10 O40 was investigated, and it was found that the structural stability of the catalyst increased by the addition of methanol. The catalyst was reused four times without significant decline in activity.